Acid‐sensing ion channel 1a drives AMPA receptor plasticity following ischaemia and acidosis in hippocampal CA1 neurons. (18th August 2015) - Quintana, Patrice; Soto, David; Poirot, Olivier; Zonouzi, Marzieh; Kellenberger, Stephan; Muller, Dominique; Chrast, Roman; Cull‐Candy, Stuart G.
Abstract : Key points: The hippocampal CA1 region is highly vulnerable to ischaemic stroke. Two forms of AMPA receptor (AMPAR) plasticity – an anoxic form of long‐term potentiation and a delayed increase in Ca 2+ ‐permeable (CP) AMPARs – contribute to this susceptibility by increasing excitotoxicity. In CA1, the acid‐sensing ion channel 1a (ASIC1a) is known to facilitate LTP and contribute to ischaemic acidotoxicity. We have examined the role of ASIC1a in AMPAR ischaemic plasticity in organotypic hippocampal slice cultures exposed to oxygen glucose deprivation (a model of ischaemic stroke), and in hippocampal pyramidal neuron cultures exposed to acidosis. We find that ASIC1a activation promotes both forms of AMPAR plasticity and that neuroprotection, by inhibiting ASIC1a, circumvents any further benefit of blocking CP‐AMPARs. Our observations establish a new interaction between acidotoxicity and excitotoxicity, and provide insight into the role of ASIC1a and CP‐AMPARs in neurodegeneration. Specifically, we propose that ASIC1a activation drives certain post‐ischaemic forms of CP‐AMPAR plasticity. Abstract: The CA1 region of the hippocampus is particularly vulnerable to ischaemic damage. While NMDA receptors play a major role in excitotoxicity, it is thought to be exacerbated in this region by two forms of post‐ischaemic AMPA receptor (AMPAR) plasticity – namely, anoxic long‐term potentiation (a‐LTP), and a delayed increase in the prevalence of Ca 2+ ‐permeable GluA2‐lacking AMPARs (CP‐AMPARs). The acid‐sensing ion channel 1a (ASIC1a), which is expressed in CA1 pyramidal neurons, is also known to contribute to post‐ischaemic neuronal death and to physiologically induced LTP. This raises the question does ASIC1a activation drive the post‐ischaemic forms of AMPAR plasticity in CA1 pyramidal neurons? We have tested this by examining organotypic hippocampal slice cultures (OHSCs) exposed to oxygen glucose deprivation (OGD), and dissociated cultures of hippocampal pyramidal neurons (HPNs) exposed to low pH (acidosis). We find that both a‐LTP and the delayed increase in the prevalence of CP‐AMPARs are dependent on ASIC1a activation during ischaemia. Indeed, acidosis alone is sufficient to induce the increase in CP‐AMPARs. We also find that inhibition of ASIC1a channels circumvents any potential neuroprotective benefit arising from block of CP‐AMPARs. By demonstrating that ASIC1a activation contributes to post‐ischaemic AMPAR plasticity, our results identify a functional interaction between acidotoxicity and excitotoxicity in hippocampal CA1 cells, and provide insight into the role of ASIC1a and CP‐AMPARs as potential drug targets for neuroprotection. We thus propose that ASIC1a activation can drive certain forms of CP‐AMPAR plasticity, and that inhibiting ASIC1a affords neuroprotection. Abstract :